Highly Productive Ice Algal Mats in Arctic Melt Ponds: Primary Production and Carbon Turnover - Hancke, Kasper; Kristiansen, Svein; Lund-Hansen, Lars Chresten (Frontiers in Marine Science, 2022)
Arctic summer sea ice extent is decreasing and thinning, forming melt ponds that cover more than 50% of the sea ice area during the peak of the melting season. Despite of this, ice algal communities in melt ponds are understudied and so are their contribution to the Arctic Ocean primary production and carbon turnover. While melt ponds have been considered as low productive, recent studies suggest that accumulated ice algal potentially facilitate high and yet overlooked rates of carbon turnover. Here we report on ice algal communities forming dense mats not previously described, collected from melt ponds in the northern Barents Sea in July. We document on distinct layered and brown colored mats with high carbon assimilation and net primary production rates compared to ice algal communities and aggregates, in fact comparable to benthic microalgae at temperate tidal flats. Rates of gross and net primary production, as well as community respiration rates were obtained from oxygen micro profiling, and carbon assimilation calculations were supported by 14C incubations, pigment analysis and light microscopy examinations. The melt pond algal mats consisted of distinct colored layers and differed from aggregates with a consisted layered structure. We accordingly propose the term melt pond algal mats, and further speculate that these dense ice algal mats may provide an important yet overlooked source of organic carbon in the Arctic food-web. A foodweb component likely very sensitive to climate driven changes in the Arctic Ocean and pan-Arctic seas.